If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.20(4x + 3) = 7 Reorder the terms: 0.20(3 + 4x) = 7 (3 * 0.20 + 4x * 0.20) = 7 (0.6 + 0.8x) = 7 Solving 0.6 + 0.8x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + -0.6 + 0.8x = 7 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + 0.8x = 7 + -0.6 0.8x = 7 + -0.6 Combine like terms: 7 + -0.6 = 6.4 0.8x = 6.4 Divide each side by '0.8'. x = 8 Simplifying x = 8
| 16(p-1)=p(p+8) | | .25(4x+12)=x+3 | | 6x+19-2x=x+16 | | 8(t-4)+4t=4(3t+3)-11 | | M(3m+1)=0 | | .5x-3=2.25+1.5x | | 1.5x+14=30 | | 6x^2+13+6=0 | | 8(w-4)=32 | | 5x-2=8x+6 | | 4(3x-8)-11x=2 | | 2y=8x+20 | | 72w^4-32w^2= | | -9f=72-f | | (x^2+4x)+(y^2-12y)=-24 | | 4n+2.5=7.3 | | 3x+50=6x | | 2x^2-8x-16y-24=0 | | -34+22=-3x+9x | | x-3/5=1/15 | | 44-50=x | | -76=(-2/3) | | 15c-8-3x=16 | | 4x^3+24x^2+36x=0 | | -3.4x-3=-2.9x+2 | | 3x+45=76,5 | | 2x^3-12x^2+18x+45=0 | | 4x^2-9=3x^2 | | d-3=-17 | | -3x+5+4x=-22+19 | | 24t^2-10t-4=0 | | x^2+1=x^2-6 |